Evaluation of Threats to Agriculture in the Totaré River Basin Due to Changes in Rainfall Patterns Under Climate Change Scenarios (2018)
In this paper we analyze the implications of different representative concentration pathway scenarios (RCP2.6, RCP4.5 and RCP8.5) on the precipitation of the Totaré River basin located in the Department of Tolima, Colombia, and its possible consequences on the productive systems of the area. In the analysis, we employed the global climatic model MPI-ESM-MR with 22 pluviographic stations of the IDEAM and the CSD (Chaotic Statistical Downscaling), a novel downscaling model for different intervals of accumulation of precipitation (5, 7, 10, 15 and 30 days). The results predict an increase of the precipitation in the Totaré River Basin from 10% to 50% for the middle and end of the century under all RCP scenarios. It is necessary to take measures to ensure adequate agricultural production due to possible flooding or soil erosion.